Predicting deterioration for the Saudi Arabia Urban Road Network - Mubaraki, Muhammad (2010)
Pavements represent an important infrastructure to all countries. In Saudi Arabia, huge investments have been made in constructing a large network. This network requires great care through conducting periodic evaluation and timely maintenance to keep the network operating under acceptable level of service. Pavement distress prediction and pavement condition prediction models can greatly enhance the capabilities of a pavement management system. These models allow pavement authorities to predict the deterioration of the pavements and consequently determine the maintenance needs and activities, predicting the timing of maintenance or rehabilitation, and estimating the long range funding requirements for preserving the performance of the network.